Knowledge, Attitudes, Perception and Reported Practices of Healthcare Providers on Antibiotic Use and Resistance in Pregnancy, Childbirth and Children under Two in Lao PDR: A Mixed Methods Study - Vanphanom Sychareun; Amphoy Sihavong; Anna Machowska; Xanded Onthongdee; Kongmany Chaleunvong; Bounxou Keohavong; Jaran Eriksen; Claudia Hanson; Manivanh Vongsouvath; Gaetano Marrone; Annelie Brauner; Mayfong Mayxay; et al. (Antibiotics, 2021)
Background: Overuse and misuse of antibiotics contribute unnecessarily to antibiotic resistance (ABR), and are thereby global health threats. Inappropriate prescriptions of antibiotics during pregnancy, delivery and early childhood are widespread across the world. This study aimed to assess knowledge, attitudes, and reported practices of healthcare providers (HCPs) and to explore their perceptions regarding antibiotic use and ABR related to pregnancy, childbirth, and children under two in Lao PDR. Methods: This is a mixed methods study with data collection in 2019 via structured interviews among 217 HCPs (medical doctors/assistant doctors, midwives/nurses, pharmacists/assistant pharmacists and drug sellers), who prescribed/dispensed antibiotics in one rural and one urban district in Vientiane province and individual qualitative interviews with 30 HCPs and stakeholders. Results: Of the HCPs, 36% had below average knowledge regarding antibiotic use and ABR, and 67% reported prescribing antibiotics for uncomplicated vaginal delivery. Half of the HCPs did not believe that their prescribing contributed to ABR, and only 9% had participated in antibiotic education. Conclusion: A substantial number of HCPs had suboptimal knowledge and prescribed antibiotics unnecessarily, thereby contributing to ABR. Continuous education and regular supervision of HCPs is recommended to improve the use of antibiotics related to pregnancy, childbirth, and young children.